HEPATOTOXICITY OF ACETAMINOPHEN TREATED BY DELONIX REGIA & AEGLE MARMELOES - Anil Kumar; Divya Sharma; Dipayan Purakayastha; Sharma, Pravesh; Mohit Khandelwal (Journal of Biomedical and Pharmaceutical Research, 2020)
Acetaminophen is commonly known as Paracetamol. It is an antipyretic drug, analgesic. It first introduced in 1955 and it cause liver toxicity, which is big issue for Patients now days also. In this work Delnix Regia and Aegle Marmeloes both the plant collected from local area Jaipur and authentify by Department of Botany, Rajasthan University, Jaipur. The authentication number is RUBL 211610 and RUBL 211611and extracted the leaves content by soxhelation process and compare them, which one is more helpful as hepatoprotective because acetaminophen drug cause toxicity in liver and for evaluation purposes different types of test like SGOT, SGPT, Total bilirubine, Total protein, molisch test, wagner test, Hager test, Benedicts test etc performed. In this work we observed that after all evaluation that Delnex Regia is more heptoprotective as compare to Aegle Marmeloes Key word: Acetaminophen, Delnix Regia, Aegle Marmeloes, Hepatotoxicity